5G Electromagnetic Radiation Attenuates Skin Melanogenesis In Vitro by Suppressing ROS Generation - Kyuri Kim; Young Seung Lee; Nam Kim; Hyung-Do Choi; Kyung-Min Lim (MDPI AG, 2022)
Recently, the impacts of 5G electromagnetic radiation (EMR) with 28 GHz on human health have been attracting public attention with the advent of 5G wireless communication. Here, we report that 5G (28 GHz) EMR can attenuate the skin pigmentation in murine melanoma cells (B16F10) and a 3D pigmented human epidermis model (Melanoderm™). B16 cells were exposed to 5G (28 GHz) with or without α-MSH for 4 h per day. Interestingly, 5G attenuated α-MSH-induced melanin synthesis. Fontana-Masson staining confirmed that the dendritic formation of α-MSH stimulated B16 cells was diminished by 5G exposure. To confirm the anti-melanogenic effect of 5G EMR, MelanoDerm™ was irradiated with 5G at a power intensity of 10 W/m2 for 4 h a day for 16 days and melanin distribution was detected with Fontana-Masson staining, which supported the anti-melanogenic effect of 5G EMR. Consistently, 5G EMR suppressed α-MSH induced upregulation of melanogenic enzymes; tyrosinase, TRP-1, and TRP-2. Of note, 5G EMR attenuated ROS production stimulated by α-MSH and H2O2, suggesting that 5G EMR may dissipate ROS generation, which is pivotal for the melanin synthesis. Collectively, we demonstrated that 5G EMR can attenuate skin pigmentation by attenuating ROS generation.